Metode Pembelajaran Tahfizh Pada Mata Pelajaran Al-Qur'an Hadis di Madrasah Ibtidaiyah - Wikanda, Fauji; Ritonga, Sahbuki; As’adurrofik, Muhammad (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study is motivated by the importance of strengthening Islamic religious education from an early age, particularly through the learning of Al-Qur'an Hadith in Islamic elementary schools (madrasah ibtidaiyah). One crucial aspect of this subject is the practice of Qur’anic memorization (tahfizh), which not only emphasizes memorizing verses but also fosters students’ religious character. However, the implementation of tahfizh methods within formal classroom settings still faces several challenges, including limited instructional time, varying memorization abilities among students, and low learning motivation. Therefore, this research aims to describe and analyze the memorization (tahfizh) methods applied in Al-Qur'an Hadith subject at Madrasah Ibtidaiyah Al-Furqon. This research employed a qualitative approach with a phenomenological method. The research site was selected purposively due to MI Al-Furqon's integrated tahfizh program within its formal curriculum. The data sources consisted of primary data obtained through interviews, observations, and documentation, and secondary data from school archives. Data were analyzed using the Miles and Huberman model, with data validity ensured through triangulation techniques. The results revealed that tahfizh teaching methods were implemented through a combination of talaqqi, sima’i, and murojaah techniques in a structured manner. The role of teachers and parental involvement were key factors in supporting the success of the program. This research contributes positively to the development of a structured and effective Qur’an memorization-based learning model in Islamic elementary education.